Peran Kejaksaan dalam Penentuan Hak Restitusi Tindak Pidana Perdagangan Orang: Studi Kasus Nomor 27/Pid.sus/2019/PN.Kpg - Agatha Melinda Soebesky Uras; Orpa Ganefo Manuain; Rosalind Angel Fanggi (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
This study aims to find out and analyze the role of the prosecutor's office in determining the right to restitution for the crime of trafficking in persons based on case number 27/Pid.sus/2019/PN.Kpg. This research is a normative legal research (library research) supported by empirical data. This research focuses on the Role of the Prosecutor's Office in Determining the Right to Restitution for the Crime of Trafficking in Persons. The approach used in this study is the case approach. This research uses primary legal materials, secondary legal materials and tertiary legal materials. This legal research is analyzed using the Content Analysis legal material analysis technique. The results of this study show that (1) The existence of restitution is contained in Law Number 21 of 2007 concerning Trafficking, Article 4 of Perma No. 1 of 2022, and is contained in the Criminal Procedure Code. (2) The role of the prosecutor's office in determining the right to restitution of victims in the crime of trafficking in persons is to inform the victim of their rights in submitting restitution applications to the court, so that the suggestions that can be given to law enforcers, especially the Public Prosecutor, should be given socialization or training regarding Law Number 21 of 2007 concerning the Eradication of Trafficking in Persons, especially the provision of restitution, so that there is a common perception in handling cases of human trafficking.